Czynniki egzogeniczne warunkujące rozwój sektora przedsiębiorstw w regionie - Sokół, Aneta (Egzogenic Factors Stimulating the Development of the Business Sector in a Region, 2009)
Because of a multitude of issues related to the development in the countryside and the huge diversity of this policy, it is difficult to presenting it in a synthetic way. There is the development of imaging equipment, on the one hand, the formation mechanisms of various kinds of difficulties in local systems, on the other showing a route out of a critical situation. Analyzed are the instruments that can be used to bring economic activity to less developed areas. Admittedly, however, is that the identification of the actual state of entrepreneurship in the regions is one of the so-called difficult socio-economic issues. With relatively many studies, which in the last decade were devoted to this subject, the vast majority deals with certain general characteristics of this phenomenon. There are only few empirical attempts of penetration, so the article is rather a modest share of research. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 840-849